2017
DOI: 10.21833/ijaas.2017.02.018
|View full text |Cite
|
Sign up to set email alerts
|

Salt and drought stress affects electron transport chain genes in rice

Abstract: Rice is well known as a salt and drought sensitive crop. Salt and drought stresses greatly affect the growth and productivity of rice plants. To study the molecular response of rice to these abiotic stresses, 14 day-old whole seedlings of the MR253 rice variety were subjected to varying duration of drought-and salt-stress treatments. Using the Differential Display Reverse Transcription Polymerase Chain Reaction (DDRT-PCR), two putative genes were identified; one encodes the apocytochrome f precursor while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…ABA is probably the most important signal molecule that controls a lot of physiological processes including stress response to abiotic stress [ 79 , 80 ], where it regulates osmotic balance and induces resistance to stresses [ 79 , 80 , 81 ]. This is achieved through the activation of antioxidant genes (CAT, SOD, peroxidase (POX)) by ABA [ 82 ] through ROS-induction and increased levels of NADPH oxidase [ 83 ]. In rice, drought-hypersensitive mutants DSM1 and DSM2 have shown the ability to regulate POX expression and control ABA levels that lead to ROS quenching [ 84 , 85 ].…”
Section: Signaling and Control In Abiotic Stress-associated Ros Homentioning
confidence: 99%
“…ABA is probably the most important signal molecule that controls a lot of physiological processes including stress response to abiotic stress [ 79 , 80 ], where it regulates osmotic balance and induces resistance to stresses [ 79 , 80 , 81 ]. This is achieved through the activation of antioxidant genes (CAT, SOD, peroxidase (POX)) by ABA [ 82 ] through ROS-induction and increased levels of NADPH oxidase [ 83 ]. In rice, drought-hypersensitive mutants DSM1 and DSM2 have shown the ability to regulate POX expression and control ABA levels that lead to ROS quenching [ 84 , 85 ].…”
Section: Signaling and Control In Abiotic Stress-associated Ros Homentioning
confidence: 99%
“…The reduction in RWC is one of the earliest responses to drought and is usually followed by a reduced leaf water potential and stomatal closing [56]. Furthermore, stomatal closing is associated with increased leaf temperatures which cause denaturation of proteins and damage membrane stability, photosynthesis, mineral nutrition, ion uptake and the synthesis of amino acids [83,84].…”
Section: Relative Water Content (Rwc)mentioning
confidence: 99%
“…Jiang and Zhang (2002) reported that inhibition of ABA synthesis reduced the activity of plasma membrane-NADPH oxidase and generation of O2 -in leaves and reciprocal effects were obtained by exogenous application of ABA. It showed that NADPH oxidase is involved in ABA induced-ROS production, which ultimately results in induction of antioxidants defense system under drought and enhance drought tolerance in rice (Varshikar and Tan, 2016).…”
Section: Ros Production Under Drought Stressmentioning
confidence: 99%